Hemoglobin level and prevalence of anemia in Soliga tribal children of Karnataka, India (South East Asia Journal of Public Health, 2017)
Hemoglobin status of tribal children in Karnataka has not been investigated adequately and extensively. Hematological parameters help to understand the normal growth and nutritional status of the children. A cross-sectional purposive sampling study was undertaken to determine the prevalence of anemia among 152 Soliga tribal children belonging to 6+ to 10+ years of Mysore district, Karnataka, India. Hemoglobin level was determined by cyanmethaemoglobin method. As per the WHO cut-off points, the children were grouped under mild, moderate and severe anemia where the level of hemoglobin below 11.5 g/dL. BMI values were estimated based on the measurements of height and weight of the children. The overall prevalence of anemia was 91.4%; 7.2% mild, 74.3% moderate, and 9.9% severe anemia. Mean hemoglobin values between boys and girls of 7+ years age group were statistically significant. A higher proportion of girls were severely anemic in the age group of 9+ and 10+ years than boys. The prevalence of different grades of anemia was more or less equally distributed among boys and girls of Soliga children. Remarkably, about 94.3% normal BMI children were anemic. Comparison of mean values of anemia and BMI between boys and girls were found statistically significant. The level of hemoglobin among Soliga Children in Karnataka is a cause for concern. Appropriate measures should be taken by the respective authorities to decrease the prevalence of anemia and improve the condition of health among the children.South East Asia Journal of Public Health Vol.6(2) 2016: 37-41